2013
DOI: 10.1007/s00221-013-3420-9
|View full text |Cite
|
Sign up to set email alerts
|

Aging-related decline in somatosensory inhibition of the human cerebral cortex

Abstract: Primary somatosensory (SI) cortical inhibition to repetitive stimuli tends to decline with increasing age. However, aging effects on the inhibition mechanism of secondary somatosensory cortex (SII) remain elusive. We aimed to study the aging-related changes of cortical inhibition in the human somatosensory system. Neuromagnetic responses to paired-pulse electrical stimulation to the median nerve were recorded in 21 young and 20 elderly male adults. Paired-pulse suppression (PPS) of SI and SII activities was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 45 publications
6
56
3
Order By: Relevance
“…It is worth noting that changes in intracortical inhibition have been associated also with physiological brain aging. However, studies in humans and animal models have shown changes in either direction (Luebke et al, 2004; McGinley et al, 2010; Schmidt et al, 2010; Marneweck et al, 2011; Cheng and Lin, 2013). On the other hand, the role of excitation has not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that changes in intracortical inhibition have been associated also with physiological brain aging. However, studies in humans and animal models have shown changes in either direction (Luebke et al, 2004; McGinley et al, 2010; Schmidt et al, 2010; Marneweck et al, 2011; Cheng and Lin, 2013). On the other hand, the role of excitation has not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data addressing this point in humans are contrasting. On the one hand, clinical electrophysiology show a decrease in paired-pulse suppression of magnetoencephalography (MEG) responses in the somatosensory cortex (Cheng and Lin, 2013). Similarly, a reduction in short-interval intracortical inhibition (SICI) of electromyographic (EMG) responses to pair of stimuli delivered to the cortex by transcranial magnetic stimulation (TMS) has been reported (Marneweck et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Paired electrical stimulation paradigm has been applied in several different clinical populations (Frasson et al, 2001;Cheng and Lin, 2013;Hsu et al, 2013) in order to examine somatosensory cortical excitability. Increased somatosensory P35m PPI ratio was observed in TLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, an ISI below 1 s would be appropriate to investigate the paired-pulse inhibition for P35m response. Several recent studies used an electrical paired pulse paradigm with ISI at 0.5 s (Wieland et al, 2008;Edgar et al, 2005;Thoma et al, 2007;Cheng and Lin, 2013;Hsu et al, 2013). Thus, a similar paradigm was used in the present study.…”
Section: Measurements Of Auditory and Somatosensory Cortex Excitabilimentioning
confidence: 95%
See 1 more Smart Citation